2012
DOI: 10.1136/medethics-2011-100217
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem brain donation and organ transplantation in schizophrenia: what about patient consent?: Figure 1

Abstract: In patients with schizophrenia, consent postmortem for organ donation for transplantation and research is usually obtained from relatives. By means of a questionnaire, the authors investigate whether patients with schizophrenia would agree to family members making such decisions for them as well as compare decisions regarding postmortem organ transplantation and brain donation between patients and significant family members. Study results indicate while most patients would not agree to transplantation or brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Following current Research in Human Subjects and HIPAA regulations, and just as in any prospective study, brain bank coordinators must seek informed consent [E] to enroll participants into the donation program. Numerous publications have detailed the consenting processes (Boyes and Ward 2003; Cruz-Sanchez et al 1997; Garrick et al 2009; Harmon and McMahon 2014; Harris et al 2013; Hawkins 2010; Porteri and Borry 2008; Samarasekera et al 2013; Strous et al 2012). Generally speaking, coordinators should inform interested candidates of their rights as research participants including confidentiality, and right to withdraw, as well as basic information about the aims and structure of the study and brain donation process.…”
Section: Enrolling Participants [A – F]mentioning
confidence: 99%
See 1 more Smart Citation
“…Following current Research in Human Subjects and HIPAA regulations, and just as in any prospective study, brain bank coordinators must seek informed consent [E] to enroll participants into the donation program. Numerous publications have detailed the consenting processes (Boyes and Ward 2003; Cruz-Sanchez et al 1997; Garrick et al 2009; Harmon and McMahon 2014; Harris et al 2013; Hawkins 2010; Porteri and Borry 2008; Samarasekera et al 2013; Strous et al 2012). Generally speaking, coordinators should inform interested candidates of their rights as research participants including confidentiality, and right to withdraw, as well as basic information about the aims and structure of the study and brain donation process.…”
Section: Enrolling Participants [A – F]mentioning
confidence: 99%
“…Despite the importance of this pre-mortem relationship, a review of the brain banking literature reveals a distinct absence of publications that outline the process of following up and keeping track of future brain donors. Much has been written about the attitudes and perceptions surrounding brain donation (Boise et al 2017a; Eatough et al 2012; Garrick et al 2003; Harris et al 2013; Lambe et al 2011; Schnieders et al 2013), what influences the decision to proceed with brain donation (Boise et al 2017b; Garrick et al 2006; Garrick et al 2009; Glaw et al 2009; Jefferson et al 2011; Schmitt et al 2001; Stevens 1998; Sundqvist et al 2012; West and Burr 2002), the consenting process itself (Benes 2005; Cruz-Sanchez et al 1997; Harmon and McMahon 2014; Porteri and Borry 2008; Strous et al 2012), brain donation as it pertains to specific diseases and controls (Adler et al 2002; Boyes and Ward 2003; Davies et al 1993; Glaw et al 2009; Haroutunian and Pickett 2007; Lim et al 1999; Schmitt et al 2001), institutional and nationwide brain banking experiences (Azizi et al 2006; Beach et al 2008; de Lange et al 2017; de Oliveira et al 2012; Grinberg et al 2007; Hulette 2003; Vonsattel et al 2008a), and brain tissue processing, practices, and need for standardization (Beach et al 2008; Cruz-Sanchez and Tolosa 1993; Dickson 2005; Graeber 2008; Palmer-Aronsten et al 2016; Ramirez et al 2018; Ravid and Ikemoto 2012; Vonsattel et al 2008b), but we found no published works focusing on donor follow-up and consequent coordination of the brain procurement. Thus, much of the literature focuses on front-end processes and back-end processes, but not the large middle-ground.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is important to consider what is owed to psychiatric patients as a community that contributes to organ donation. Current regulations allow individuals with affective and psychotic disorders to serve as organ donors for both living and deceased organ donation without qualification on the grounds of their psychiatric conditions [ 29 , 30 ]. While the role of reciprocity in organ donation is the subject of current debate, our willingness to accept organs from mentally ill donors surely imparts a moral obligation on the medical community to ensure that this patient population receives fair consideration when in need of organ transplants.…”
Section: Main Textmentioning
confidence: 99%